2018
DOI: 10.1159/000490073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics Analysis of Korean Patients with Stargardt Disease Using Targeted Exome Sequencing

Abstract: Purpose: To investigate genetic mutations in Korean patients with Stargardt disease (STGD) using exome sequencing, and to analyze the correlations between genetic mutations and clinical phenotypes. Methods: Peripheral venous blood was obtained from 24 clinically diagnosed Korean STGD patients, followed by extraction of genomic DNAs. Using exome sequencing we investigated gene mutations for the adenosine triphosphate-binding cassette, subfamily A, member 4 (ABCA4) elongation of very-long-chain fatty acids 4 (EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Especially in Asia, the causative genes of STGD other than ABCA4 are rarely found 232526. In a recent study that included clinically diagnosed Korean STGD patients, 17 out of 24 (70.8%) patients were detected to have ABCA4 mutations 8. No potential mutations in the ELOVL4 and PROM1 were, however, found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in Asia, the causative genes of STGD other than ABCA4 are rarely found 232526. In a recent study that included clinically diagnosed Korean STGD patients, 17 out of 24 (70.8%) patients were detected to have ABCA4 mutations 8. No potential mutations in the ELOVL4 and PROM1 were, however, found.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the genetic and phenotypic heterogeneity, identification of the causative genetic variants linked to IRD is needed for the accurate diagnosis and treatment of these patients. As the next-generation sequencing (NGS) technology, which can save tremendous cost and time as compared to the previous technologies, has rapidly developed, identification of the causative genes responsible for IRD has dramatically improved 4567891011. To date, about 270 genes have been identified as the cause of IRD in accordance with RetNet database (https://sph.uth.edu/retnet/).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the incidents of STGD-associated variants in ABCA4 were 70.5% in the Russian Federation, 70.8% in Korea, 67% in Portugal, and 60.5% in Spain (Fumagalli et al, 2001;Maia-Lopes et al, 2009;Riveiro-Alvarez et al, 2009;Sung, Choi, Shim, & Song, 2019;Zolnikova et al, 2017). In previous studies, the incidents of STGD-associated variants in ABCA4 were 70.5% in the Russian Federation, 70.8% in Korea, 67% in Portugal, and 60.5% in Spain (Fumagalli et al, 2001;Maia-Lopes et al, 2009;Riveiro-Alvarez et al, 2009;Sung, Choi, Shim, & Song, 2019;Zolnikova et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we identified eight families (66.67%) with disease‐causing variants in the ABCA4 gene. In previous studies, the incidents of STGD‐associated variants in ABCA4 were 70.5% in the Russian Federation, 70.8% in Korea, 67% in Portugal, and 60.5% in Spain (Fumagalli et al., ; Maia‐Lopes et al., ; Riveiro‐Alvarez et al., ; Sung, Choi, Shim, & Song, ; Zolnikova et al., ). This study also showed no potential variants in other Stargardt‐like‐associated genes, which is consistent with the findings in a previous study on Chinese patients (Xin et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…Stargardt disease is the most common autosomal recessive type of juvenile-onset macular dystrophy, with an estimated prevalence of 1: 8,000 to 1: 10,000 individuals (1) . Described in 1909 by Karl Stargardt (2) , the disease is bilateral and symmetrical in appearance and its main feature is the decrease in central vision that starts around the first or second decade of life (3,4) . The typical finding at the eye fundus is a pigmentary maculopathy, which manifests itself as a decreased foveal reflex, pigment mottling, beaten-bronze reflex, and bull's eye pigment appearance; furthermore, it can progress to macular atrophy.…”
Section: Introductionmentioning
confidence: 99%